(untitled) (Journal of the College of Basic Education, 2022)
The research aims to identify the effect of a counseling program based on counseling in reality for the development of willpower among university students, and for the purpose of verifying this goal, the researcher deduced the following null hypotheses: A -There are no statistically significant differences at the level of significance (05.0) between the average scores of the experimental group students before and after applying the realistic counseling method according to the willpower scale. B -There are no statistically significant differences at the level of significance (05.0) between the mean scores of the experimental group and the average scores of the control group in the post test according to the willpower scale. C- The size of the effect caused by the independent variable (the indicative program) on the dependent variable (will-power) among university students. The current research is limited to male and female students of the faculties of Al-Mustansiriya University for morning studies for the academic year 2020-2021The researchers used the quasi-experimental approach, and chose the design of the experimental by comparing the results of the post test for the experimental and control groups. Willpower after applying the indicative program, and this difference is in favor of the experimental group, that is, in favor of the post test, which means that the program used in the current research has an impact on the development of willpower. As for the second hypothesis, its results showed that there are statistically significant differences at the level of significance (0.05(.Between the average ranks of the scores of the students of the experimental group and the average ranks of the scores of the students of the control group on the dimensional willpower scale after applying the counseling program, and the results of the third hypothesis showed that there are statistically significant differences in the effect of the counseling program based on counseling in reality caused by the independent variable in the level of the dependent variable in the strength of Will, the researchers mentioned a set of recommendations and proposals